2018
DOI: 10.1038/s41366-018-0014-4
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-related acetylcholinesterase elevation is reversed following laparoscopic sleeve gastrectomy

Abstract: Obesity-related AChE resistance phenotype may be reversed following LSG and correlates with metabolic outcomes. Further long-term studies will be needed to validate and evaluate the beneficial effect of AChE reduction post bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…NR3C1, which is targeted by He Ye, is related to the etiology of obesity, the control of which will lead to an improvement in obesity-related disorders (Majer-Łobodzińska and Adamiec-Mroczek, 2017). Moreover, DDP4 (targeted by Zhi Qiao) and ACHE (targeted by Ling Zhi) play a significant role in obesity, and modulating their activity may be of great utility in obesity treatment (Valerio et al, 2017; Shenhar-Tsarfaty et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…NR3C1, which is targeted by He Ye, is related to the etiology of obesity, the control of which will lead to an improvement in obesity-related disorders (Majer-Łobodzińska and Adamiec-Mroczek, 2017). Moreover, DDP4 (targeted by Zhi Qiao) and ACHE (targeted by Ling Zhi) play a significant role in obesity, and modulating their activity may be of great utility in obesity treatment (Valerio et al, 2017; Shenhar-Tsarfaty et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The altered expression of genes including ERBB2 [ 38 ], DACT1 [ 39 ], ARAP1 [ 40 ], MYH9 [ 41 ], INPPL1 [ 42 ], SARM1 [ 43 ], NOTCH1 [ 44 ], ROBO1 [ 45 ], MAPK8IP1 [ 46 ], ANK1 [ 47 ], SARM1 [ 43 ], SREBF2 [ 48 ], SIK1 [ 49 ], PASK (PAS domain-containing serine/threonine kinase) [ 50 ], NOS2 [ 51 ], OAS3 [ 52 ], KL (klotho) [ 53 ], PECAM1 [ 54 ], S100A12 [ 55 ], S100P [ 56 ], BATF3 [ 57 ], PLEK (pleckstrin) [ 58 ], ALOX5 [ 59 ], ARG1 [ 60 ], CXCL8 [ 61 ], CXCR1 [ 62 ], PTAFR (platelet-activating factor receptor) [ 63 ], PYGL (glycogen phosphorylase L) [ 64 ], TCF4 [ 65 ], CAMP (cathelicidin antimicrobial peptide) [ 66 ], RUNX2 [ 67 ], PLA2G2A [ 68 ], GCG (glucagon) [ 69 ], RARRES2 [ 70 ] and HAP1 [ 71 ] in diabetes mellitus was reported to be an independent prognostic factors. ACHE (acetylcholinesterase) [ 72 ], FGFR3 [ 73 ], VLDLR (very-low-density lipoprotein receptor) [ 74 ], SHC1 [ 75 ], HDAC6 [ 76 ], CHRNA2 ...…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA expression of ACHE was significantly upregulated in response to acute AC2-26 treatment, in the current study. Previous studies have suggested impaired sympathetic/parasympathetic response and reduced cholinergic blockade may be responsible for the inflammation and adverse metabolic sequelae observed in obesity [ 80 ]. However, short-term cholinergic blockade with atropine; a competitive antagonist of the acetylcholine receptor enhanced insulin sensitivity in both human lean and abdominal obese subjects [ 81 ].…”
Section: Discussionmentioning
confidence: 99%